2013
DOI: 10.1093/toxsci/kft172
|View full text |Cite
|
Sign up to set email alerts
|

The Nrf2 Activator, tBHQ, Differentially Affects Early Events Following Stimulation of Jurkat Cells

Abstract: Nuclear factor erythroid 2-related factor 2 (Nrf2) is a transcription factor that is activated by cellular stresses, such as oxidative compounds. After activation, Nrf2 induces transcription of its target genes, many of which have cytoprotective functions. Previously, we have shown that activation of Nrf2 by tert-butylhydroquinone (tBHQ) skews murine CD4⁺ T-cell differentiation. Although the role of Nrf2 in murine T cells is somewhat characterized, it is largely uncharacterized in human T cells. Therefore, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 28 publications
0
44
0
Order By: Relevance
“…Consistent with other cell types, tBHQ treatment increased expression of the Nrf2 target genes, heme oxygenase 1 (HMOX-1), NAD(P)H quinone oxidoreductase 1 (NQO1), and glutamate-cysteine ligase, catalytic subunit (GCLC), in human peripheral blood mononuclear cells (Fig. 1) [15, 16]. In addition, tBHQ caused a modest induction of NRF2 mRNA expression itself, which has also been observed previously in primary mouse T cells and suggests that NRF2 upregulates itself.…”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations
“…Consistent with other cell types, tBHQ treatment increased expression of the Nrf2 target genes, heme oxygenase 1 (HMOX-1), NAD(P)H quinone oxidoreductase 1 (NQO1), and glutamate-cysteine ligase, catalytic subunit (GCLC), in human peripheral blood mononuclear cells (Fig. 1) [15, 16]. In addition, tBHQ caused a modest induction of NRF2 mRNA expression itself, which has also been observed previously in primary mouse T cells and suggests that NRF2 upregulates itself.…”
Section: Resultsmentioning
confidence: 55%
“…Our previous studies showed the Nrf2 activator tBHQ inhibited IL-2 production in activated Jurkat T cells, but the effect of tBHQ on primary human T cells has not been fully characterized [16]. Therefore, we determined the effect of tBHQ treatment on IL-2 production by PBMCs activated with anti-CD3/anti-CD28, a T cell specific activator.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We adapted this approach by visualizing Nrf2 activation in real time in single cells by placing the expression of the fluorescent protein mApple under the control of the ARE sequence. To validate the ARE_mApple reporter gene, HEK293 cells were cotransfected with Venus, as a morphology marker, and ARE_mApple and treated with tertiary butylhydroquinone (tBHQ), an activator of endogenous Nrf2 (26). At 24 h posttransfection, cells were imaged, and ARE_mApple fluorescence was measured.…”
Section: Resultsmentioning
confidence: 99%